Description new Species of the Spider Hasarius Adansoni ( AUDOUIN 1826) (ARANEAE: SALTICIDAE) - Hala G .Noori, Zeina N. Al-Azawii, (Pakistan Journal of Medical & Health Sciences, 2022)
A new species of the spider Hasarius adansoni sp.nov, was described for the first time in Iraq which are collected from Baghdad from Dora city .This Hasarius adansoni is a genus of jumping spiders have eight eyes with long legs covered in spines and hair the male Hasarius adansoni spiders are black in color with white crescents in their body crescent is present on the back part of the head, and another one on the front part of the opisthosoma and pedipalps that are partly white male Hasarius adansoni have two small white dots on the posterior back and two even smaller ones towards the end whereas the female Hasarius adansoni spiders are dark brown in color and crescent is present on the back part of the head with a lighter and somewhat rufous opisthosoma. Keywords: Crescent, Epigone, Pedipalps, Salticidae, Silk